ANALISIS PEMASARAN KEDELAI (Glicyne max L. Merril) DI KABUPATEN SUKOHARJO - SETYOWATI SETYOWATI (Universitas Sebelas Maret, 2010)
This research aims are (1) to find out the soybean marketing channel in Regency Sukoharjo, (2) to analyze the size of margin, cost and profit of soybean marketing in soybean marketing agency and marketing channel levels in Regency Sukoharjom (3) to analyze the efficiency level of soybean marketing in Regency Sukoharjo viewed from economical aspect.